2022
DOI: 10.1111/ejn.15800
|View full text |Cite
|
Sign up to set email alerts
|

Brain entropy, fractal dimensions and predictability: A review of complexity measures for EEG in healthy and neuropsychiatric populations

Abstract: While electroencephalography (EEG) signals are commonly examined using conventional linear methods, there has been an increasing trend towards the use of complexity analysis in quantifying neural activity. On top of revealing complex neuronal processes of the brain that may not be possible with linear approaches, EEG complexity measures have also demonstrated their potential as biomarkers of psychopathology such as depression and schizophrenia. Unfortunately, the opacity of algorithms and descriptions originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 229 publications
(361 reference statements)
1
74
0
Order By: Relevance
“…Mediano et al (2021) showed that in MEG within 0.5 – 30Hz, active tasks actually exhibited lower complexity values compared to rested wakefulness. In addition, a recent review from Lau et al (2022) discussed several studies that reported apparently contradicting modulations of neural complexity in different clinical conditions, where some report lower and others higher levels of complexity. Thus, the question whether higher neural complexity can always be clearly interpreted as more complex or irregular brain activity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediano et al (2021) showed that in MEG within 0.5 – 30Hz, active tasks actually exhibited lower complexity values compared to rested wakefulness. In addition, a recent review from Lau et al (2022) discussed several studies that reported apparently contradicting modulations of neural complexity in different clinical conditions, where some report lower and others higher levels of complexity. Thus, the question whether higher neural complexity can always be clearly interpreted as more complex or irregular brain activity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since REM sleep (sometimes called ‘paradoxical sleep’; Peigneux et al, 2001 or Siegel, 2011) is characterized by wake-like, but non-oscillatory brain activity (Blumberg et al, 2020; Peever & Fuller, 2017), these disparate results between the two frequency ranges suggest that the narrowband slope mainly measures non-oscillatory, aperiodic brain activity. The relative increase in broadband complexity during REM sleep has been attributed to higher levels of conscious content that accompany vivid dreaming and thus require more complex brain activity than deeper, mostly dreamless sleep stages (Lau et al, 2022; Mateos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, regularity measures investigate a lower level of details in the time-frequency domain, in favor of higher robustness. For this reason, they are applicable to noisier or smaller time series (which are typical of biosignals), for which predictability measures could not be reliably calculated [33]. Therefore, in recent years, new metrics for measuring regularity have been proposed.…”
Section: Review Of Complexity Measures For the Analysis Of Eeg Signalsmentioning
confidence: 99%
“…Non-linear analyses (particularly among advanced EEG signal-processing techniques) investigate the complex emergent phenomena underlying chaotic dynamical systems, providing the possibility to analyze the strong complexity and irregularity of neuronal activities of the brain. These analyses are of extreme importance in order to identify the process of cognitive impairment [ 33 ]. Indeed, the complexity measures of EEG signals could enhance and provide more reliable results than traditional EEG analysis techniques (e.g., event-related potential, time, and frequency analysis) in the studies of psycho-pathological conditions [ 34 ] and the diagnosis of disorders [ 35 ].…”
Section: Introduction and Motivation Of The Workmentioning
confidence: 99%